From knowledge to action: understanding Ghanaian physicians responses to COVID-19 pandemic threats - Wutor, Victor C.; N’guessan, Benoit B. (International Journal Of Community Medicine And Public Health, 2024)
Background: This study, conducted with meticulous care, aimed to determine the knowledge, perception, and preparedness of Ghanaian physicians towards a pandemic or another wave of COVID-19. Methods: The study, conducted between May and July 2023, used a robust methodology and included a comprehensive questionnaire. The questionnaire was distributed through Facebook, WhatsApp, and other social media links, ensuring a broad reach and diverse participation. Results: A total of 777 physicians responded, and participation was from all 16 regions of Ghana. Of these, 372 (47.9%) were males, while 405 were females (52.1%). The survey, consisting of 55 questions about COVID-19 knowledge, 29 questions about perception, and 21 questions about preparedness, was designed to capture a comprehensive understanding. The study’s inclusion criteria were limited to physicians who had direct contact with patients in medical facility settings. The findings revealed that Ghanaian physicians ranked high regarding their knowledge of COVID-19. However, their readiness to face another pandemic challenge was observed at 47% in progress. In comparison, 43% of physicians responded as done, with another 10% not being unaware of the current situation about preparedness. Conclusions: In conclusion, this study sheds light on the nuanced responses of Ghanaian physicians to the COVID-19 pandemic threats, emphasizing the critical role of knowledge in shaping their actions. Through a qualitative exploration, we discerned a spectrum of reactions ranging from proactive measures to adaptive strategies in navigating the uncertainties of the crisis. Ghana needs a blueprint for pandemic management.